Trends and challenges for sustainable development of sheep and goat systems - Arsenos G.; Vouraki S.; Ragkos A.; Theodoridis A. (Pastoralism and sustainable development: proceedings, 2021)
Sheep and goat farming systems in Europe are essential part of the agricultural industry providing ecosystem services to society. The sector faces many and diverse challenges. The main problem is low income despite heavy reliance on subsidies of Common Agricultural Policy (CAP). The notion is that subsidies under CAP will be directed at public goods (GHG, Biodiversity, animal welfare and rural livelihoods). Poor uptake of innovations and lack of new entrants are also obstacles for progress in the industry. Our objective is to give an overview of present challenges, trends and opportunities of the sheep and goat industry. A new paradigm for the future is proposed based on key findings of the project “Innovation for Sustainable Sheep and Goat Production in Europe; iSAGE”. iSAGE, assessed the sustainability of the sector to future challenge such as climate change, food security, resource use efficiency and rural deprivation in marginal regions. The results showed that emphasis should be given to (i) supporting supply chains and increasing consumption of sheep and goat products through novel labelling, packaging and cuts, (ii) address climate change and greenhouse gas emissions using novel methodologies and technologies, and informing relevant policies particularly in pastoral systems, (iii) breeding for enhanced animal resilience, efficiency and adaptability, and promoting region-specific use of local breeds, and (iv) adoption of relevant innovations.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)